2012
DOI: 10.1002/jobm.201100480
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of pyrene and benzoate in Mycobacterium isolate KMS is regulated differentially by catabolic repression

Abstract: The soil isolate, Mycobacterium sp. strain KMS, utilizes an array of carbon compounds including the aromatics benzoate and pyrene as sole carbon sources. Growth on pyrene induced both chromosomal and plasmid nidA genes encoding pyrene ring‐hydroxylating dioxygenase α‐subunits for pyrene oxidation. Diauxic growth occurred when KMS was cultured with pyrene plus either acetate, succinate, fructose, or benzoate and nidA expression only was detected in the second slower log‐phase period. Potential cAMP‐CRP binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
(77 reference statements)
0
4
0
1
Order By: Relevance
“…This lack of transcriptional induction also suggests that rhizodeposits did not trigger a massive carbon catabolite repression (CCR), which would expectedly yield lower transcription of PAH-RHD genes in planted soil. Purified sugars and root extracts have been shown to inhibit the degradation of aromatic compounds by CCR in several cultivated isolates (Keuth and Rehm, 1991 ; Dal et al, 2002 ; Kamath et al, 2004 ; Rentz et al, 2004 ; Rojo, 2010 ; Zhang and Anderson, 2013 ; Vandera et al, 2015 ). However, it has been suggested that CCR may be more significant when considering a single species of degrader rather than a diverse community (Martin et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…This lack of transcriptional induction also suggests that rhizodeposits did not trigger a massive carbon catabolite repression (CCR), which would expectedly yield lower transcription of PAH-RHD genes in planted soil. Purified sugars and root extracts have been shown to inhibit the degradation of aromatic compounds by CCR in several cultivated isolates (Keuth and Rehm, 1991 ; Dal et al, 2002 ; Kamath et al, 2004 ; Rentz et al, 2004 ; Rojo, 2010 ; Zhang and Anderson, 2013 ; Vandera et al, 2015 ). However, it has been suggested that CCR may be more significant when considering a single species of degrader rather than a diverse community (Martin et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, it seems clear that Bz is a distinctive preferred substrate for several soil bacteria. There are, of course, examples of simultaneous degradation in Bz-containing mixtures (14,44), including synergic interactions such as those described in Sagittula stellata E-37, a member of the Roseobacter lineage, where increased growth rates are found for Bz-4-Hb mixtures (45). There are several possible explanations for the preference for Bz over AC, none of them fully satisfactory.…”
Section: Figmentioning
confidence: 99%
“…Diauxic growth has been reported for the pyrene-degrading isolate Mycobacterium sp. KMS [43, 44] but this nutritional strategy is not used by the model mycobacteria M. smegmatis or M.…”
Section: Discussionmentioning
confidence: 99%